Development of a Modified Talaqqi Model in al-Qur’an Recitation Art (Tausyih) with Bayāti Rhythm: A Case Study of Students at Baitul Qurro al-Qur’an Boarding School, Jakarta - Wahyuningsih, Shinta; Dwirahayu, Gelar; Ghofur, Abdul (Pendidikan Agama Islam STIT Palapa Nusantara, 2026)
This study is motivated by the limited research on the application of modified Talaqqi methods in al-Qur’an recitation, particularly in mastering the Bayāti rhythm, despite its significant impact on students’ Qur’anic reading skills. The study aims to develop and evaluate a Modified Talaqqi Model to enhance both melodic and vocal performance among students. Adopting a qualitative case study design, the research involves 20 students from Baitul Qurro al-Qur’an Boarding School, Jakarta, selected through purposive sampling. Data were collected using direct observation, performance recordings, and evaluation rubrics, and were analyzed using descriptive statistics and qualitative interpretation to assess mastery of melodic patterns and vocal quality. The findings reveal that students achieved high proficiency in song (melodic pattern) and voice quality, with overall average scores of 96.05/100, and that the model effectively improved mastery of the Bayāti rhythm, vocal clarity, and tajwid application. These results confirm the effectiveness of the modified Talaqqi method when combined with audio-visual supports such as QR codes and guitar chords. The study concludes that the Modified Talaqqi Model significantly enhances al-Qur’an recitation skills, providing theoretical contributions to Qur’anic arts education and practical guidance for instructors, and suggests that future research examine its applicability to other rhythms and larger student populations.